Folded Sandwich Protective Structures against Blast and Impact Loads - Li, Zhejian (Curtin University, 2019)
In this thesis, novel folded truncated pyramid structures and a bi-directional load-self-cancelling square dome structure are proposed as the core of light-weight protective sandwich structures to resist blast and impact loads. Analytical derivations, numerical simulations, quasi-static and dynamic crushing tests are carried out to examine the dynamic crushing behaviours and energy absorption capacities of various designs for developing the best-performing core structures for blast and impact load resistance.